CT virtual intravascular endoscopy in the visualization of fenestrated endovascular grafts - Sun, Zhonghua; Allen, Yvonne; Sanjay, N.; Knight, R.; Hartley, D.; Lawrence-Brown, M. (International Society of Endovascular Specialists, 2008)
Purpose: To report the diagnostic value of computed tomographic (CT) virtual intravascular endoscopy (VIE) in the assessment of patients with abdominal aortic aneurysm (AAA) treated with fenestrated endovascular grafts.Methods: Eight patients (7 men; mean age 76 years, range 70?82) with AAAs unsuitable for open surgery or conventional endovascular repair had fenestrated endovascular grafts implanted. Both pre- and post-fenestration multislice CT data were used to generate VIE images of the visceral artery ostia and the side branch fenestrated stents. CT VIE images were compared with conventional 2-dimensional (2D) axial CT and multiplanar reformatted (MPR) images for the ability to visualize the intraluminal appearance of stents, as well as to measure the length of stents that protruded into the aortic lumen.Results: Various fenestrations were deployed in 27 aortic branches. Scalloped and large fenestrations were implanted in 6 side branch ostia, respectively, and small fenestrations in 15 renal artery ostia. Fewer than half of the stents (37%) were found to be circular on VIE images, while the remaining stents were flared to varying extents at the inferior portion. The majority (96%) of stents protruded into the lumen up to 7.0 mm. Although the configuration of the side branch ostia changed to a variable extent, no significant difference was apparent between the diameters of branch ostia before and after fenestration (p>0.05). Conclusion: Our preliminary study shows that VIE proved superior to conventional 2D or MPR images in visualizing the final configuration of the fenestrated vessels and was comparable to the other techniques in measuring stent protrusion into the aortic lumen. VIE could be a valuable technique to identify any suspected abnormalities associated with fenestrated endovascular grafts by demonstrating the final intraluminal configuration of the stents in the fenestrated vessels.